Silk fibroin-based topological structure conductive hydrogel as well as preparation method and application thereof

By constructing an rGO@SilMA-PEGDA interpenetrating network and using DLP printing technology, a silk fibroin-based topological conductive hydrogel with high precision and excellent mechanical properties was prepared. This solved the mechanical and electrical shortcomings of existing hydrogels, enabling the precise fabrication of complex three-dimensional structures and expanding its application in the fields of biomedicine and flexible electronics.

CN120818247AActive Publication Date: 2025-10-21ZHEJIANG KING LABLE TECH CO LTD

Patent Information

Application Number
CN202511059280.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-10-21
Estimated Expiration
2045-07-30

AI Technical Summary

Technical Problem

Existing silk fibroin hydrogels have deficiencies in mechanical properties and conductive stability, making it difficult to meet the application requirements of high-precision sensing. Traditional preparation methods also make it difficult to achieve precise preparation of complex three-dimensional topological structures.

Method used

Using rGO@SilMA-PEGDA interpenetrating network structure and DLP high-precision printing technology, combined with phenyl-2,4,6-trimethylbenzoylphosphate lithium photoinitiator, silk fibroin-based conductive hydrogels with Gyroid, Diamond, or Schwarz topologies were prepared.

Benefits of technology

It significantly improves the mechanical properties and sensing stability of hydrogels, enabling high-precision printing of complex three-dimensional structures. It solves the problems of non-uniform conductivity and structural uniformity of traditional hydrogels, expanding their applications in the fields of biomedicine and flexible electronics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818247A_ABST
    Figure CN120818247A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flexible electronic materials, and discloses a silk fibroin-based topological structure conductive hydrogel and a preparation method and application thereof.The silk fibroin-based topological structure conductive hydrogel is prepared from rGO-coated SilMA serving as a polymerization main body, the rGO-coated SilMA is formed by mixing silk fibroin and graphene oxide dispersion liquid and reacting in the presence of methacrylic acid glyceride, and the rGO-coated SilMA is prepared through the steps that the rGO-coated SilMA serves as the polymerization main body; according to the invention, rGO (at) SilMA is taken as a substrate, polyethylene glycol diacrylate is taken as a reinforcing phase, phenyl-2, 4, 6-trimethylbenzoyl lithium phosphate (LAP) is taken as a photoinitiator, and the mass ratios of all the components in the photocuring ink are as follows: 20% of rGO (at) SilMA, 10% of PEGDA and 0.75% of LAP. The rGO-coated SilMA-PEGDA interpenetrating network structure is constructed and TPMS topological design is introduced, so that the mechanical property and sensing stability of the hydrogel are remarkably improved, the compression modulus is improved by the interpenetrating network, the elongation at break is kept at a high level, the high-deformation scene requirement is met, the stress distribution is more uniform by the negative Gaussian curvature characteristic of the topological structure, and the effective sensing area is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flexible electronic materials, and in particular to a silk fibroin-based topologically structured conductive hydrogel and a preparation method and application thereof. Background Art

[0002] Flexible conductive hydrogels, a class of functional materials that combine biocompatibility and electrical responsiveness, show broad application prospects in wearable health monitoring devices, human-computer interaction systems, and flexible robotics. Hydrogels based on natural biopolymers, due to their excellent biosafety, have become a core material of choice for skin electronics and implantable sensing devices.

[0003] Silk fibroin (SF), a natural protein, possesses a unique β-pleated crystalline structure and excellent biocompatibility. Modified SilMA, obtained through methacrylation, not only retains the original bioactivity of silk fibroin but also introduces photocrosslinkable acrylate groups, making it suitable for precision 3D printing. However, a single SilMA network has limitations in mechanical properties, and its fracture strain and elastic modulus are difficult to meet the requirements of high-deformation scenarios.

[0004] In existing technologies, researchers often use composite modification strategies to improve the performance of silk fibroin hydrogels, but many problems still exist: some schemes use toxic cross-linking agents such as glutaraldehyde, which poses a risk of cytotoxicity; conductive fillers such as graphene oxide (GO) tend to aggregate in hydrogels, resulting in uneven conductivity; most hydrogels are two-dimensional structures or rely on mold molding, with a single structural design, making it difficult to achieve precise preparation of complex three-dimensional topological structures.

[0005] 3D printing technology, particularly digital light processing (DLP) photocuring technology, offers the potential for the fabrication of complex hydrogel structures thanks to its high printing precision and rapid molding speed. However, existing silk fibroin-based hydrogel inks offer insufficient printing resolution, and the molded hydrogels struggle to balance mechanical properties with conductive stability, limiting their application in high-precision sensing.

[0006] Therefore, it is of great significance to develop a silk fibroin-based topological conductive hydrogel with high printing accuracy, excellent mechanical properties and stable conductive properties. Summary of the Invention

[0007] The purpose of the present invention is to solve the above problems and to propose a silk fibroin-based topological conductive hydrogel and its preparation method and application.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions: A silk fibroin-based topological conductive hydrogel, comprising the following components: rGO@SilMA (reduced graphene oxide-methacrylated silk fibroin composite system) is used as the polymer host, wherein the rGO@SilMA is formed by mixing silk fibroin with graphene oxide (GO) dispersion and reacting them in the presence of glycerol methacrylate (GMA); Polyethylene glycol diacrylate (PEGDA) is the reinforcing phase; Lithium phenyl-2,4,6-trimethylbenzoyl phosphate (LAP) was used as a photoinitiator; The mass proportions of each component in the photocurable ink are: rGO@SilMA 20%, PEGDA 10%, and LAP 0.75%; the hydrogel has a Gyroid (G), Diamond (D), or Schwarz (S) topological structure.

[0009] A method for preparing a silk fibroin-based topologically conductive hydrogel, based on the silk fibroin-based topologically conductive hydrogel according to claim 1, comprising the following steps: S1: Extraction and degumming of silk fibroin: 40 g of raw silk was added to 2 L of boiling water containing 10 g of anhydrous sodium carbonate and boiled for 30 min. After removal, the silk was repeatedly scrubbed with deionized water for 3 times. After drying, the degumming step was repeated 3 times to obtain degummed silk fibroin. S2: Preparation of rGO@SilMA solution: 20 g of degummed silk fibroin was dissolved in 100 mL of 9.3 M lithium bromide solution, heated at 60 °C for 1 h and stirred every 20 min; 100 mL of GO dispersion and 6 mL of LMA were added, and the mixture was stirred at 60 °C and 300 rpm for 6 h. The reaction solution was dialyzed for 24 h using a dialysis bag with a molecular weight cutoff of 12-14 kDa, filtered three times through a filter cloth and a 150-mesh filter, frozen at -80 °C, and lyophilized for 5 days to obtain rGO@SilMA dry powder. S3: Preparation of photocurable ink: 2.7 mL of distilled water was mixed with 0.3 mL of PEGDA, 0.0225 g of LAP was added and stirred in the dark until dissolved, then 0.6 g of GO@SilMA powder was added and stirred at 300 rpm until completely dissolved to obtain rGO@SilMA-PEGDA photocurable ink; S4: 3D printing of topological hydrogels: design of G, D or S topological structures; The photocurable ink was injected into the DLP printer tank for printing, and then washed with deionized water after printing to obtain the target hydrogel.

[0010] Preferably, the concentration of the GO dispersion in step S2 is 0.5% w / v, and the reduction reaction is achieved through tyrosine residues in silk fibroin.

[0011] Preferably, the molecular weight of the PEGDA in step S3 is 700 Da.

[0012] Preferably, the topological structure model in step S4 is designed by nTop software, and the unit cell size is 16×10×2 mm.

[0013] Preferably, the parameters of DLP printing in step S4 are: light intensity 15-20 mW / cm², slice layer thickness 15 μm, pulling speed 3-6 mm / min, and exposure time 2-8 s.

[0014] Application of a silk fibroin-based topological conductive hydrogel in the preparation of wearable biosensors, human-computer interaction equipment or flexible electronic devices.

[0015] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. This invention significantly improves the mechanical properties and sensing stability of the hydrogel by constructing an rGO@SilMA-PEGDA interpenetrating network structure and introducing a TPMS topological design. The interpenetrating network increases the compression modulus and maintains a high elongation at break, meeting the requirements of high-deformation scenarios. The negative Gaussian curvature of the topological structure ensures more uniform stress distribution and increases the effective sensing area. 2. The present invention uses tyrosine residues of silk fibroin to in situ reduce GO to form rGO conductive pathways. Combined with DLP high-precision printing technology, the sensor sensitivity (GF) is improved, and the printing accuracy can reach the micron level, which can accurately form complex three-dimensional structures. This not only solves the problem of uneven conductivity of traditional hydrogels, but also expands its application scenarios in the fields of biomedicine and flexible electronics. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 A schematic diagram showing the response of the relative change rate of resistance of hydrogels with different topological structures (G, D, S) provided according to an embodiment of the present invention is shown; Figure 2 A schematic diagram showing the resistance response speed and cycle stability of hydrogels with different topological structures (G, D, S) provided in an embodiment of the present invention is shown; Figure 3 A schematic diagram showing the application of hydrogels with different topological structures (G, D, S) provided by an embodiment of the present invention in the fields of human physiological signal monitoring and speech recognition is shown; Figure 4 A schematic diagram showing the application of hydrogels with different topological structures (G, D, S) provided by an embodiment of the present invention in the field of wearable sports monitoring is shown; Figure 5A schematic diagram showing the application of hydrogels with different topological structures (G, D, S) provided by an embodiment of the present invention in the new interactive field of wearable devices is shown. DETAILED DESCRIPTION

[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0017] Example 1 Raw material dosage: 40 g raw silk, 10 g anhydrous sodium carbonate, 100 mL 9.3 M lithium bromide solution, 100 mL 0.5% w / v GO dispersion, 6 mL glycerol methacrylate (GMA), 0.3 mL PEGDA with a molecular weight of 700 Da, 0.0225 g LAP, and appropriate amount of deionized water.

[0018] Preparation process: The steps described in the invention were followed. First, silk fibroin was extracted and degummed to obtain approximately 25g of degummed silk fibroin. An rGO@SilMA solution was then prepared, followed by degumming, dissolution, reaction, dialysis, filtration, and freeze-drying to obtain rGO@SilMA powder. A light-curable ink was then prepared, mixing and dissolving the rGO@SilMA powder, PEGDA, and LAP in appropriate proportions. Finally, a Gyroid (G) topological structure model was designed using nTop software. DLP printing parameters were set to an illumination intensity of 18mW / cm², an exposure time of 5s, and a pull-up speed of 4.5mm / min to print a G-structured silk fibroin-based topological conductive hydrogel.

[0019] Example 2 The amount of raw materials used is the same as in Example 1.

[0020] Preparation process: The extraction and degumming of silk fibroin, preparation of the rGO@SilMA solution, and preparation of the photocurable ink were the same as in Example 1. A Diamond (D) topological structure model was designed using nTop software, and the DLP printing parameters were the same as in Example 1 to print a D-structured silk fibroin-based topological conductive hydrogel.

[0021] Example 3 The amount of raw materials used is the same as in Example 1.

[0022] Preparation process: The extraction and degumming of silk fibroin, preparation of the rGO@SilMA solution, and preparation of the photocurable ink were the same as in Example 1. The Schwarz (S) topological structure model was designed using nTop software, and the DLP printing parameters were the same as in Example 1 to print an S-structured silk fibroin-based topological conductive hydrogel.

[0023] Comparative Example 1 Amount of raw materials: compared with Example 1, no PEGDA was added, and the amounts of other raw materials were the same.

[0024] Preparation process: The preparation steps of Example 1 were followed, except that PEGDA was not added during the photocurable ink preparation step.

[0025] Comparative Example 2 Raw material dosage: Compared with Example 1, no GO dispersion was added, and the dosage of other raw materials was the same.

[0026] Preparation process: The preparation steps of Example 1 were followed, except that GO dispersion was not added in the preparation step of rGO@SilMA solution.

[0027] Comparative Example 3 The amount of raw materials used is the same as in Example 1.

[0028] Preparation process: The extraction and degumming of silk fibroin, preparation of the rGO@SilMA solution, and preparation of the light-curable ink were the same as in Example 1. The light-curable ink was poured into a conventional mold and cured under the same lighting conditions as in Example 1, without DLP 3D printing or topological structure design.

[0029] Performance Testing Mechanical properties test: The compression modulus and fracture strain of the hydrogel were tested using a universal testing machine in accordance with relevant standard methods, and the test data were recorded.

[0030] Conductive performance and sensing sensitivity test: The resistance change of the hydrogel under different strains was measured by the four-probe method, and the relative resistance change rate and sensitivity (GF) were calculated to analyze its conductive performance and sensing sensitivity.

[0031] Response speed and cycle stability test: A dynamic mechanical analyzer and an electrochemical workstation were used to test the response time and recovery time of the hydrogel when subjected to external force, as well as the performance changes after multiple cycles.

[0032] The test results are shown in the following table:

[0033] The test results show that the silk fibroin-based topological conductive hydrogels obtained in Examples 1-3 outperformed Comparative Examples 1-3 in terms of compression modulus, fracture strain, sensitivity, response speed, and cyclic stability. The compression modulus of Examples 1-3 was significantly higher than that of Comparative Example 1 because the addition of PEGDA formed an interpenetrating network structure, effectively improving the mechanical properties of the hydrogel. Compared with Comparative Example 2, the sensitivity of Examples 1-3 was significantly improved due to the addition of GO dispersion and the uniform dispersion of rGO. However, Comparative Example 3, due to the lack of topological structural design and 3D printing technology, had a lower response speed and cyclic stability than the Examples. This fully demonstrates the effectiveness and superiority of the technical solution of the present invention.

[0034] GO is conductive because it is covalently reduced through the amino acid residues on silk during the SiIMA dialysis process, and the reaction conditions are very mild.

[0035] application The silk fibroin-based topological conductive hydrogel prepared by the present invention has important application value in multiple fields.

[0036] Attachment Figure 1 (a) is the relationship between the strain and resistance change rate of the G structure, (b) is the relationship between the strain and resistance change rate of the D structure, (c) is the relationship between the strain and resistance change rate of the S structure, (d) is the relationship between the pressure and resistance change rate of the G structure, (e) is the relationship between the pressure and resistance change rate of the D structure, and (f) is the relationship between the pressure and resistance change rate of the S structure.

[0037] The ac graph shows that the relative rate of change of resistance of all three structures increases with increasing strain: the G structure responds rapidly in the low-strain region, then levels off, ultimately stabilizing at approximately 70%; the D structure changes more slowly, also ultimately reaching 70%; the S structure shows a similar trend to the G structure, but ultimately falls slightly below 70%, indicating that all three structures respond to strain, albeit with varying rates and magnitudes. The df graph demonstrates that under pressure, the G structure's resistance change rate exhibits a good linear relationship with pressure in the low-pressure region (0-600 Pa), then stabilizes beyond this pressure; the D structure's resistance change rate increases slowly and remains linear in the high-pressure region; and the S structure responds rapidly in the low-pressure region and stabilizes after reaching a certain pressure.

[0038] In the field of human body signal detection, the three topologies of G, D, and S each offer advantages: the G structure is sensitive to low-strain and low-pressure signals and responds quickly, making it suitable for detecting weak signals such as pulse or muscle contraction, and can be integrated into wearable devices to monitor physiological parameters in real time; the D structure has a slower response but a wide linear range, making it suitable for monitoring continuous and gentle pressure signals (such as the pressure distribution caused by prolonged sitting), helping to prevent health problems; the S structure responds quickly at low pressures and can detect sudden instantaneous pressure (such as sports shock), making it suitable for early warning systems in protective equipment. Analysis of the characteristics of these structures provides new material and structural options for human body signal detection technology.

[0039] Attachment Figure 2 (a) is the resistance response speed of the G structure, (b) is the resistance stability of the G structure, (c) is the strain (10%, 20%, 30%) and the resistance change rate of the G structure, (d) is the resistance response speed of the D structure, (e) is the resistance stability of the D structure, (f) is the strain (10%, 20%, 30%) and the resistance change rate of the D structure, (g) is the resistance response speed of the S structure, (h) is the resistance stability of the S structure, and (i) is the strain (10%, 20%, 30%) and the resistance change rate of the S structure.

[0040] A 16×10×2mm sheet structure was constructed. This structure offers increased flexibility and thinness, allowing it to better conform to the curves of the human body, significantly improving wearer comfort while also enhancing signal acquisition stability and accuracy. In terms of response time, the G structure (105ms response / 440ms recovery) is suitable for capturing transient signals; the D structure (171ms response / 258ms recovery) is more suitable for monitoring regular signals; and the S structure (167ms response / 21ms recovery) excels in rapid, frequent detection scenarios. Cyclic stability testing showed that the G structure maintained good short-term stability over 1,000 cycles, while the D structure exhibited stable fluctuations, making it suitable for long-term monitoring. The S structure even remained stable after 10,000 cycles. Overall, the G structure is suitable for detecting sudden, transient signals (such as transient physiological changes), while the D structure is suitable for continuous, daily monitoring (such as fitness tracking). The S structure, with its fast response, ultra-short recovery, and excellent long-term stability, meets the needs of high-precision medical monitoring (such as chronic disease management).

[0041] Attachment Figure 3 (a) is swallowing monitoring, and (b) is speech recognition.

[0042] G-structured conductive hydrogels have demonstrated significant application value in the fields of human physiological signal monitoring and speech recognition. In physiological monitoring, the hydrogel, by fitting onto the neck, detects in real time the resistance changes caused by swallowing. This non-invasive and real-time monitoring method can be applied in medical rehabilitation, providing objective data support for evaluating the effectiveness of rehabilitation training for patients with swallowing dysfunction. It can also serve as an auxiliary tool for the clinical diagnosis of swallowing dysfunction. In speech recognition, the hydrogel can accurately distinguish the resistance change characteristics of the pronunciation of the numbers 1 through 9. It can be used as a new voice sensing material in wearable interactive devices, such as smart home control and contactless human-computer interaction systems in special environments (such as high noise or hand-impaired operation), with the advantages of high efficiency and precision.

[0043] Attachment Figure 4 (a) The good deformation rate and elastic recovery of the conductive hydrogel with a ring topology, (b) the signal generated by the bending of the conductive hydrogel with a ring topology.

[0044] A ring-shaped D-structured conductive hydrogel can monitor finger bending and movement in real time through changes in resistance. When the finger bends, the hydrogel stretches and deforms, causing a corresponding change in resistance. By analyzing the resistance change curve, finger movements can be precisely tracked. This property makes it widely applicable in wearable motion monitoring, such as enabling precise hand motion capture in virtual reality (VR) interactive devices, enhancing the immersive experience. In medical rehabilitation, it can quantify and evaluate hand training data, providing objective evidence for doctors to develop personalized rehabilitation plans.

[0045] Attachment Figure 5 (a) shows the conductive hydrogel adhering to copper foil after being soaked in tannic acid (TA), (b-c) show the electronic keyboard adhering to the skin, (d) is a schematic diagram of the electronic keyboard structure, and (e) shows different resistance signals when pressing the electronic keyboard.

[0046] By adjusting structural parameters (such as wall thickness) to control sensing properties, S-structured conductive hydrogels can be fabricated into skin-attached electronic keyboards. When subjected to the same pressure at different locations, the hydrogel produces differential resistance changes, which are then converted into electrical signals for command input. This design provides a new interactive method for wearable devices (such as smart bracelets and smart clothing), enabling convenient control without traditional input devices, significantly enhancing the practicality and functionality of wearable technology.

[0047] The above description of the embodiments is intended to enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to the embodiments shown herein but is intended to conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A silk fibroin-based topological conductive hydrogel, characterized in that: It is composed of the following components: rGO@SilMA (reduced graphene oxide-methacrylated silk fibroin composite system) is used as the polymer host, wherein the rGO@SilMA is formed by mixing silk fibroin with graphene oxide (GO) dispersion and reacting them in the presence of glycerol methacrylate (GMA); Polyethylene glycol diacrylate (PEGDA) is the reinforcing phase; Lithium phenyl-2,4,6-trimethylbenzoyl phosphate (LAP) was used as a photoinitiator; The mass proportions of each component in the photocurable ink are: rGO@SilMA 20%, PEGDA 10%, and LAP 0.75%; the hydrogel has a Gyroid (G), Diamond (D), or Schwarz (S) topological structure.

2. A method for preparing a silk fibroin-based topologically conductive hydrogel, based on the silk fibroin-based topologically conductive hydrogel according to claim 1, characterized in that: The following steps are involved: S1: Extraction and degumming of silk fibroin: 40 g of raw silk was added to 2 L of boiling water containing 10 g of anhydrous sodium carbonate and boiled for 30 min. After removal, the silk was repeatedly scrubbed with deionized water for 3 times. After drying, the degumming step was repeated 3 times to obtain degummed silk fibroin. S2: Preparation of rGO@SilMA solution: 20 g of degummed silk fibroin was dissolved in 100 mL of 9.3 M lithium bromide solution, heated at 60 °C for 1 h and stirred every 20 min; 100 mL of GO dispersion and 6 mL of LMA were added, and the mixture was stirred at 60 °C and 300 rpm for 6 h. The reaction solution was dialyzed for 24 h using a dialysis bag with a molecular weight cutoff of 12-14 kDa, filtered three times through a filter cloth and a 150-mesh filter, frozen at -80 °C, and lyophilized for 5 days to obtain rGO@SilMA dry powder. S3: Preparation of photocurable ink: 2.7 mL of distilled water was mixed with 0.3 mL of PEGDA, 0.0225 g of LAP was added and stirred in the dark until dissolved, then 0.6 g of GO@SilMA powder was added and stirred at 300 rpm until completely dissolved to obtain rGO@SilMA-PEGDA photocurable ink; S4: 3D printing of topological hydrogels: design of G, D or S topological structures; The photocurable ink was injected into the DLP printer tank for printing, and then washed with deionized water after printing to obtain the target hydrogel.

3. The method for preparing a silk fibroin-based topologically conductive hydrogel according to claim 2, characterized in that: The concentration of the GO dispersion in step S2 is 0.5% w / v, and the reduction reaction is achieved through the tyrosine residues in the silk fibroin.

4. The method for preparing a silk fibroin-based topologically conductive hydrogel according to claim 2, characterized in that: The molecular weight of the PEGDA in step S3 is 700 Da.

5. The method for preparing a silk fibroin-based topologically conductive hydrogel according to claim 2, characterized in that: The topological structure model described in step S4 is designed using nTop software, and the unit cell size is 16×10×2 mm.

6. The method for preparing a silk fibroin-based topologically conductive hydrogel according to claim 2, characterized in that: The DLP printing parameters in step S4 are: light intensity 15-20 mW / cm², slice thickness 15 μm, pulling speed 3-6 mm / min, and exposure time 2-8 s.

7. Use of the silk fibroin-based topological conductive hydrogel according to claim 1 in the preparation of wearable biosensors, human-computer interaction equipment or flexible electronic devices.

Citation Information

Patent Citations

  • Silk fibroin / carbon material conductive hydrogel as well as preparation and application thereof

    CN113292744A

  • Method for preparing biological tissue engineering scaffold by using dual-network hydrogel with good mechanical property and high cell proliferation capacity

    CN115779147A

  • 3D printing silk fibroin-based conductive hydrogel as well as preparation method and application thereof

    CN120424372A

  • Photocurable bioink with electroconductivity and a preparation thereof

    KR102180865B1

Cited By

  • Preparation method of conductive hydrogel capable of triggering double-drug time sequence delivery through electrical stimulation and application of conductive hydrogel in wound healing

    CN122229814A